The Deliberative City - Hoi Kong (The Windsor Yearbook of Access to Justice, 2010)
In this paper, I will argue that general administrative law concerns about the legitimacy and effectiveness of rule-making have special force in the municipal zoning by-law context. In particular, I will argue that a particular, civic republican conception of legitimate state action offers the best justification for municipal regulation and provides the best normative foundation for developments in municipal consultation processes. In Part II, I will argue that the consultative processes in Quebec’s zoning laws reflect a commitment to civic republican ideals, but that because of specific features of municipal regulation, these ideals are incompletely realized. In Part III, I will argue that a particular municipal institution – the ward council – enables the zoning process to better approximate civic republican ideals. I conclude this paper by arguing that ward councils not only strengthen the normative justifications for municipal regulation, they contribute to its effectiveness.